Keputusan Memilih Umat Islam dalam Pemilu Legislatif 2024: Citra Kandidat dan Religiusitas - Kodansyah, Riska; Nursalim Malay, M; Natalia, Angga (Universitas Islam Negeri Raden Intan Lampung, 2025)
Elections are an important indicator of democratic governance in a country. Decisions taken during elections are a form of